CORRELATION OF SERUM ZINC LEVEL WITH HISTOPATHOLOGICALLY DIAGNOSED DIFFERENT VARIANT OF LEPROSY - PRAMILA JAIN,; ASHISH KOSHTI,; REENI MALIK,; BHAWNA BHIMTE, (International Journal of Pharma and Bio Sciences, 2014)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae. Leprosy involves multiple organs (skin, nerves, liver and kidney), that leads to a wide range of biochemical as well as immunological changes in the body including trace elements such as zinc, cooper and magnesium. Low serum zinc concentrations are found in various physiological as well as pathological conditions such as in Pregnancy and lactation, amongst pure alcoholics, people suffering from gastrointestinal and liver disease and in cases of sickle cell disease. Low serum zinc level in leprosy patients also is shown by various workers. Present study included 63 newly diagnosed leprosy cases compared to matched controls. This study was undertaken to know the histopathological features of leprosy in skin biopsies of newly diagnosed patients, to categorize them into various subtypes based on histomorphological features, to correlate with clinical presentations wherever possible and to investigate the level of serum zinc in leprosy. In the present study serum zinc level was found to be significantly reduced (P value < 0.05) i.e. 0.001 in all the 63 patients of leprosy.